Double Infections of Rehmannia mosaic virus and Potato virus Y on Tobacco Plants in Central Java and Special Region of Yogyakarta - Tika Pramudya Wardani; Sedyo Hartono; Sri Sulandari; Susamto Somowiyarjo (Jurnal Perlindungan Tanaman Indonesia, 2021)
Various viruses can cause mosaic disease on tobacco plants. Proper detection of the cause of the mosaic disease helps determine effective control. The purpose of this study was to detect the presence of double infection of Rehmannia mosaic virus (ReMV) with Potato virus Y (PVY) using multiplex RT-PCR in tobacco plants from Central Java and Special Region of Yogyakarta. The viral suspension was inoculated on Chenopodium amaranticolor to obtain one viral colony from one local lesion. The multiplex RT-PCR method using Tobamovirus primers (TobRT-up1 and TobRT-do2) and Potyvirus primers (MJ1 and MJ2) can detect double infection caused by ReMV with PVY in tobacco plants distributed in Central Java and Special Region of Yogyakarta. The multiplex RT-PCR product showed that tobacco samples with mosaic symptoms from Temanggung, Klaten, Bantul, and Kalasan were positive ReMV. Multiplex RT-PCR has successfully detected double infection of ReMV and PVY on tobacco samples from Klaten and Kalasan. ReMV Bantul, Kalasan, and Klaten were homolog to ReMV USA isolate and ReMV Temanggung was homolog to ReMV Japanese isolate. PVY Klaten was homolog to PVY Turkey isolate, and PVY Kalasan was homolog to PVY Iran.